Interaksi Sosial dan Bentuk Inklusivitas Mahasiswa Papua dalam Lingkungan Kampus - Sahara Lani Lestari; Dinda Syafitri; Kayla Amelia Putri; Farzad Sahnadi Pasaribu; Muhammad Farrel Evan Yuri; Arung Buana Subuh (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The campus is a meeting place for various cultures due to the diverse backgrounds of its students. As a result, social interactions that can foster a sense of togetherness and mutual respect are necessary. This study focuses on the experiences of Papuan students at the State University of Medan (UNIMED), known as the Character Building University, particularly how they adapt and interact in the campus environment. This study uses a descriptive qualitative approach involving in-depth interviews and observations to describe how Papuan students adapt, the initial problems they face, such as differences in dialect, communication style, and academic activity dynamics, as well as the elements that help them build good social relationships. The results of the study show that Papuan students are able to establish positive relationships with their environment, even though the initial adaptation process is rather difficult. They increase their confidence and communicate better with others through academic activities such as discussions, group work, and presentations. Overall, the experience of interaction on campus greatly helps Papuan students become more adaptive, inclusive, and in line with UNIMED's character building objectives.